Calculation of Electricity Losses in Non-Symmetric Mode - Begmatova Mukhlisa Mutalibjon kizi; Begmatova Mukhlisa Mutalibjon kizi; Sharofov Salokhiddin Sirojidinovich (Genius Journals, 2023)
In this article, the solution of problems associated with the loss of electrical energy in asymmetrical modes was considered. The article provided general information about the structure of electrical energy losses, studied the types of electrical energy losses and methods for calculating electrical energy losses in asymmetric modes
Keywords: asymmetrical mode; power supply; low voltage